Plasma Energy-Balance Metabolites Discriminate Asymptomatic Patients with Peripheral Artery Disease - Hernández-Aguilera, Anna; Fernández-Arroyo, Salvador; Cabre, Noemí; Luciano-Mateo, Fedra; Baiges-Gaya, Gerard; Fibla, Montserrat; Martín-Paredero, Vicente; Menendez, Javier A.; Camps, Jordi; Joven, Jorge (Mediators of Inflammation, 2018)
Peripheral artery disease (PAD) is a common disease affecting 20–25% of population over 60 years old. Early diagnosis is difficult because symptoms only become evident in advanced stages of the disease. Inflammation, impaired metabolism, and mitochondrial dysfunction predispose to PAD, which is normally associated with other highly prevalent and related conditions, such as diabetes, dyslipidemia, and hypertension. We have measured energy-balance-associated metabolite concentrations in the plasma of PAD patients segregated by the severity of the disease and in plasma of healthy volunteers using a quantitative and targeted metabolomic approach. We found relevant associations between several metabolites (3-hydroxybutirate, aconitate, (iso)citrate, glutamate, and serine) with markers of oxidative stress and inflammation. Metabolomic profiling also revealed that (iso)citrate and glutamate are metabolites with high ability to discriminate between healthy participants and PAD patients without symptoms. Collectively, our data suggest that metabolomics provide significant information on the pathogenesis of PAD and useful biomarkers for the diagnosis and assessment of progression.